Halal Image in Product Acceptance: A Comparative Study from Muslim Majority and Minority Countries - Azhary, Riza Aulia; Rizkina, Nya’ Soraya (Program Studi Perbankan Syariah FEBIII UIN Ar-Raniry, 2026)
The development of Islamic branding and strategic marketing has skyrocketed over the past decades. Islamic branding companies started to expand their targeted market into the non- Muslim majority countries. This research aims to identify the most significant determinants of brand acceptance and rejection, specifically in Islamic branding, by measuring intention to buy as the determinant of buying behaviour. Utilising the extended theory of Ajzen’s Theory of Planned Behaviour, by measuring the 3 factors constructed by the theory (attitude to behaviour, subjective norm, perceived behavioural control) and the halal image determiner, the research examined the correlation between the four independent variables and the intention to buy. Using quantitative methods and an online questionnaire, the paper found that subjective norm and perceived behavioural control are 2 significant determinants of intention to buy. In addition, based on the sample collected, it is to be noted that there is a significant disparity in the perspective of marketing by being a Muslim and a non-Muslim, as the result showed religion as a significant factor for implementing certain marketing strategies.